A Compositional Proof System for the Modal mu-Calculus - Andersen, Henrik Reif; Stirling, Colin; Winskel, Glynn (BRICS Report Series, 1998)
We present a proof system for determining satisfaction between processes in a fairly general process algebra and assertions of the modal mu-calculus. The proof system is compositional in the structure of processes. It extends earlier work on compositional reasoning within the modal mu-calculus and combines it with techniques from work on local model checking. The proof system is sound for all processes and complete for a class of finite-state processes.